Lung function, forced expiratory volume in 1 s decline and COPD hospitalisations over 44 years of follow-up - Zaigham, Suneela; Wollmer, Per; Engström, Gunnar (The European respiratory journal, 2016)
The use of baseline lung function in the prediction of chronic obstructive pulmonary disease (COPD) hospitalisations, all-cause mortality and lung function decline was assessed in the population-based “Men Born in 1914” cohort. Spirometry was assessed at age 55 years in 689 subjects, of whom 392 had spirometry reassessed at age 68 years. The cohort was divided into three groups using fixed ratio (FR) and lower limit of normal (LLN) criterion: forced expiratory volume in 1 s (FEV 1 )/vital capacity (VC) ≥70%, FEV 1 /VC <70% but ≥LLN (FR + LLN − ), and FEV 1 /VC <70% and <LLN (FR + LLN + ). Over 44 years of follow-up, 88 men were hospitalised due to COPD and 686 died. Hazard ratios (95% CI) for incident COPD hospitalisation were 4.15 (2.24–7.69) for FR + LLN − and 7.88 (4.82–12.87) for FR + LLN + (reference FEV 1 /VC ≥70%). Hazard ratios for death were 1.30 (0.98–1.72) for FR + LLN − and 1.58 (1.25–2.00) for FR + LLN + . The adjusted FEV 1 decline between 55 and 68 years of age was higher for FR + LLN − and FR + LLN + relative to the reference. Of those with FR + LLN − at 55 years, 53% had progressed to the FR + LLN + group at 68 years. Airflow obstruction at age 55 years is a powerful risk factor for future COPD hospitalisations. The FR + LLN − group should be carefully evaluated in clinical practice in relation to future risks and potential benefit from early intervention. This is reinforced by the increased FEV 1 decline in this group.